2013
DOI: 10.3126/nepjoph.v5i1.7819
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival impression cytology in computer users

Abstract: We found that those who used computers daily for long hours developed more CIC changes than those who worked at the computer for a shorter daily duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Conjunctival impression cytology has a wide range of applications in ophthalmology. It facilitates the diagnosis of ocular surface disorders [6,7]. Results of this study showed that, in a total of 30 patients studied, there were 18 patients with a positive burning sensation (60.0%) and 12 with were negative (40.0%), 22 (73.3%) had negative lacrimation and 8 were positive (26.7%), 17 patients (56.7%) had positive blurring of vision and 13 patients were negative (43.3%), 18 patients had negative photophobia (60.0%) and 12 Patients were positive (40.0%), 23 had negative eye redness (76.7%) and 7 patients were positive (23.3%), and 15 patients had positive Gritty sensation (50.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival impression cytology has a wide range of applications in ophthalmology. It facilitates the diagnosis of ocular surface disorders [6,7]. Results of this study showed that, in a total of 30 patients studied, there were 18 patients with a positive burning sensation (60.0%) and 12 with were negative (40.0%), 22 (73.3%) had negative lacrimation and 8 were positive (26.7%), 17 patients (56.7%) had positive blurring of vision and 13 patients were negative (43.3%), 18 patients had negative photophobia (60.0%) and 12 Patients were positive (40.0%), 23 had negative eye redness (76.7%) and 7 patients were positive (23.3%), and 15 patients had positive Gritty sensation (50.0%).…”
Section: Discussionmentioning
confidence: 99%
“…CIC findings were reported to be showing mild dysplasia in 25 (16.66%), moderate 7(4.66%), severe 3(2%), acute inflammatory lesions 5(3.33%) & a cellular 31 (20.66%). Kumar S. et al did impression cytologyin computer users and control group [10] . CIC results in control group were of stage 0 and stage I, while in computer user group showed results between stage II to stage IV.…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival impression cytology (CIC), a non-invasive simple technique has been employed to examine the conjunctival changes in dry eye. 1,2…”
Section: Introductionmentioning
confidence: 99%